Simultaneous ammonia stripping and anaerobic digestion for efficient thermophilic conversion of dairy manure at high solids concentration. (15th December 2017) - Yao, Yiqing; Yu, Liang; Ghogare, Rishikesh; Dunsmoor, Alexander; Davaritouchaee, Maryam; Chen, Shulin
Abstract: A major challenge to take high rate advantage of thermophilic anaerobic digestion (AD) is overcoming ammonia inhibition without adding any significant cost to the process. A concept of thermophilic AD with simultaneous ammonia stripping was tested for treating dairy manure at high total solids concentration (TS%) as an attempt to address this challenge. The results showed that ammonia inhibition occurred at 1.8–2.4 g/L total ammonia nitrogen (TAN) concentration which corresponded to 10% TS as a threshold concentration. Thermophilic AD of dairy manure efficiency at the threshold TS% was significantly improved by simultaneously stripping ammonia with the optimum stripping rate of 1 L min −1 . The required time for reaching stable state was 4 days shorter than control, and the highest methane content (56.5–75.5%) was obtained. The ammonia stripping strategy maintained TAN level below the inhibition limit of 1.5 g/L throughout AD process. The maximum cumulative methane production of 192.3 L/kg-volatile solids (VS) was obtained, which was 2.3-fold the control. Therefore, simultaneous ammonia stripping overcame the ammonia inhibition on thermophilic AD of dairy manure at the threshold TS%. The proposed concept simplified the system by combining ammonia stripping and thermophilic AD within the same digester. Highlights: High ammonia concentration inhibit thermophilic anaerobic digestion at total solids contents above 10%. Simultaneous ammonia stripping adopted overcame the ammonia inhibition. Optimal stripping rate led to the maximum methane production (192.3 L/kg VS). The approach simplified the operational process as a single digester.